2019
DOI: 10.4103/jips.jips_181_18
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary hollow-bulb obturator: A paradigm shift

Abstract: Maxillary defects, whether congenital or acquired, make a patient encounter an array of physical and psychological difficulties, leading to an extremely poor quality of life. Rehabilitation of such a patient is often challenging due to the extent of the defect area coupled with the absence of adequate retention caused by the size and weight of the prosthesis. Further, providing a proper seal of the oronasal communication is of utmost importance to restore function. Taking the above factors into consideration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Large-sized maxillectomy defects often result after surgical treatment of mucormycosis, and the duration of healing in such defects is determined not only by the aggressive nature of the lesion, but also by the postoperative care [39]. As confirmed by the majority of reports in this review [16,[19][20][21][22]25,31,32,34,39], weight reduction is critically important when the prosthesis is suspended without much remnant bone and tooth support. As a result, in such cases, a hollow bulb design should be used [17,23,24,27,32,36,[39][40][41][42].…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Large-sized maxillectomy defects often result after surgical treatment of mucormycosis, and the duration of healing in such defects is determined not only by the aggressive nature of the lesion, but also by the postoperative care [39]. As confirmed by the majority of reports in this review [16,[19][20][21][22]25,31,32,34,39], weight reduction is critically important when the prosthesis is suspended without much remnant bone and tooth support. As a result, in such cases, a hollow bulb design should be used [17,23,24,27,32,36,[39][40][41][42].…”
Section: Resultsmentioning
confidence: 74%
“…The details on the sites of the defect and types of prosthetic treatment provided are summarized in Table 1. A total of 30 articles [13,14,[23][24][25][26][27][28][29][30][31][32]15,[33][34][35][36][37][38][39][40][41][42][16][17][18][19][20][21][22] on prosthetic rehabilitation in the orofacial region after surgical treatment of mucormycosis published during the 12-year study period were reviewed. Of the 30 articles, 19 reported mucormycosis in diabetic patients, 2 described mucormycosis specifically as a post-COVID 19 complication, and 25 were reports from India.…”
Section: Resultsmentioning
confidence: 99%
“…Closed bulb obturator was provided, to prevent accumulation of fluid or food debris thereby enhancing phonetics. 10 Heat polymerized PMMA resin was used for fabrication with cast partial framework because of its evident superior mechanical, physical, and biological properties. A chromecobalt metal framework provided more durability and was designed to ensure uniform stress distribution to remaining natural teeth and supporting structures within physiologic limits.…”
Section: Discussionmentioning
confidence: 99%
“…14 more cases could be found on PubMed (Table 1) and 5 on google scholar (Supplementary table with references) with same etiology and treatment during the same time frame (2007-2019). [4][5][6][7][8][9][10][11][12][13][14][15][16] In addition, Abu El-Naaj et al (2013) have reported 5 patients with history of mucormycosis who succumbed to the disease before they could be rehabilitated with maxillary obturator. 5 I. E. Ali, et al reported prosthodontic rehabilitation of post mucormycosis defects from 30 case reports published between 2010 to 2021.…”
Section: Data Acquisition and Observationsmentioning
confidence: 99%